Збірка есеїстики О. Забужко «З мапи книг і людей» у системі підготовки майбутніх журналістів - Свалова, Марина І.; Svalova, M. І. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглядається збірка есеїстики О. Забужко «З мапи книг і людей» у контексті вивчення журналістської майстерності та редакторського аналізу в ЗМК. Розкриваються основні форми роботи з публіцистичними текстами письменниці (аналіз актуальності теми, проблемно-тематичного наповнення, жанрових особливостей; створення студентами власного журналістського матеріалу). In the current article author observes collection of the essays «From the map of books and peoples» by O. Zabuzhko in the context of forming of abilities and skills in textual editing in mass media. Researcher discovers basic forms of work with publicistic texts of writer (analysis of actuality of topic, problematic and topical content, genre features, creation of own journalistic material by the students). Author examines such features of the publicism of O. Zabuzhko as actuality, analysis of creative way of artist (in a wide meaning) in the context of epoch, combination of journalistic and artistic origins. In the article researcher proposes the example of the practical class, where lecturer can apply work with texts of writer and also with the texts created by students based on the essays of O. Zabuzhko.
Collection of the Essays «From the Map of Books and Peoples» by O. Zabuzhko in the System of Future Journalists’ Education
Keywords: есеїстика; essay writing; публіцистика; publicism; актуальність теми; actuality of topic; проблематика; problems; редакторський аналіз; editorial analysis